One Little Word - Coelho, Joseph,Colpoys, Allison (Quarto Publishing Group UK, 2023)
The next picture book from Waterstones Children's Laureate, Joseph Coelho and Allison Colpoys, One Little Word is a powerful and poetic story about two best friends who are forced apart by a big argument that turns up in the form of a hairy monster. Cover – One Little Word.
Description based on publisher supplied metadata and other sources
Keywords: Stories in rhyme